Poster Presentations for UK Conference events 2022: Hydrogen homes and social acceptance in the United Kingdom - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2022)
These contributions represent findings from a series of online focus groups conducted with members of the UK public (n=58) between February and April, 2022. The study set out to better understand consumer attitudes towards the proposition of converting the national gas grid to enable a domestic hydrogen future; composed of hydrogen home appliances for space heating, hot water, and cooking. The posters show that that future heating systems should ensure thermal comfort, ease of use, energy efficiency, and smart performance, while providing space savings and noise reduction, alongside demonstrable environmental benefits. For cooking systems, consumers wish to preserve the best features of gas, such as speed, responsiveness, and controllability, but also desire the potential safety and aesthetic benefits of electric systems, principally induction hobs. For the most part, hydrogen heating and cooking appear welcome prospects for natural gas users, with no discernible preference for hobs over boilers, or vice-versa. Notwithstanding, careful attention is needed to understand the interplay between static and dynamic factors, such as personal values and beliefs, and changes in culture and energy markets. Furthermore, hydrogen policy should align to ensuring greater transparency concerning the benefits, costs, and risks of the transition. This involves clearer explanation regarding the justification and implications of hydrogen production pathways and emerging hydrogen geographies. The analysis concludes that consumer heterogeneity must be internalized into policymaking to enact socially acceptable transition pathways for the UK housing stock.
Keywords: Hydrogen acceptance; Social barriers; Low-carbon homes; Heat decarbonisation; Consumer preferences